Elements of health literacy as a tool for health promotion - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula Jolanta (Journal of Education, Health and Sport, 2017)
The use of health literacy in health promotion is quite a new issue, just developing. Literacy is associated primarily with the human reading and writing skills, but it also has a shift in the sphere of health. Health literacy is a much broader concept than alphabetism. This includes not only reading and writing skills, but also the decision-making and broadcasting of own health.